Sooka Super Series Volleyball Malaysia / Ahmad Hafizuddin Ahmad Shukri and Mohamad Mukri Nabil Azmi - Ahmad Shukri, Ahmad Hafizuddin; Azmi, Mohamad Mukri Nabil (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Sooka was launched the opening Sooka Super Series Volleyball (SSSVB 2022) season on Friday at Dewan Besar Tanjung in Seksyen 19, Shah Alam, in collaboration with Astro Arena and the Malaysian Volleyball Association (MAVA). The first event, which will take place from October 14th to November 6th, and will feature seven local teams, including SAC Selangor Lion, Melaka Mousedeer, Kuala Lumpur Shark, Sarawak Hornbill, ATM Gladiator, Sabah Rhino, and Johor Tiger, as well as an overseas team, Amelia Indonesia. SSSVB 2022’s main objective is, according to MAVA president Hean Boon Yeow, to promote the local team worldwide. There are teams featuring foreign players from the USA, Thailand, India, and Sri Lanka, which will excite the action, and the addition of Amelia Indonesia will undoubtedly present to expose competition to the local teams.